The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1111/nph.18752
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis NPF2.13 functions as a critical transporter of bacterial natural compound tunicamycin in plant–microbe interaction

Abstract: Summary Metabolites including antibiotics, enzymes, and volatiles produced by plant‐associated bacteria are key factors in plant–microbiota interaction that regulates various plant biological processes. There should be crucial mediators responsible for their entry into host plants. However, less is known about the identities of these plant transporters. We report that the Arabidopsis Nitrate Transporter1 (NRT1)/NPF protein NPF2.13 functions in plant uptake of tunicamycin (TM), a natural antibiotic produced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…1b; Table 2) 3), it is likely under control rather than a spontaneous diffusion of the compound. A recent study showed that tunicamycin can be transported by a plant Nitrate Transporter1/Peptide Transporter Family (NPF1/NPF) protein NPF2.13 in plant-microbe interaction (Liu et al, 2023). Also, tunicamycin is produced by Streptomyces species which are abundant in soil microorganisms (Takatsuki et al, 1971).…”
Section: Forummentioning
confidence: 99%
“…1b; Table 2) 3), it is likely under control rather than a spontaneous diffusion of the compound. A recent study showed that tunicamycin can be transported by a plant Nitrate Transporter1/Peptide Transporter Family (NPF1/NPF) protein NPF2.13 in plant-microbe interaction (Liu et al, 2023). Also, tunicamycin is produced by Streptomyces species which are abundant in soil microorganisms (Takatsuki et al, 1971).…”
Section: Forummentioning
confidence: 99%